You Are Not Here: Sartre’s Phenomenological Ontology and the Architecture of Absence - Susan Herrington (Footprint)
This paper examines Jean-Paul Sartre’s phenomenological ontology in relationship to experiences with architecture that account for absence. While interest in Sartre’s phenomenology has waned over the past thirty years, philosophers of art are revisiting his work, particularly the way imagination figures in his phenomenology. As educators, students, and practitioners who have the task of imagining what could be, Sartre’s grasp of the imagining consciousness in experience is especially relevant. His three main forms of the imagining consciousness – negation, nothingness, and being – are explored in the context space, place, and location. These forms of consciousness are drawn from his major phenomenological studies regarding the imagination, Being and Nothingness: An Essay on Phenomenological Ontology (1943; 1956), The Imaginary (1940; 2004), and Critique of Dialectical Reason (1960; 1976). Examples of absence include in-situ memorial structures that literally provide the space for negation, sites of religious veneration that render the place of nothingness, and spontaneous memorials that serve as the location for being (pour-soi, en-soi, and pour-autrui). Ultimately, Sartre’s phenomenological ontology reveals that imagination plays a vital role in understanding the experiential power of architecture in relationship to space, place, and location. In doing so, this paper also suggests that the imagining conscious itself may be an important part of an ontology of architecture.